Adherence to Iron and Folic Acid Supplementation and Its Associated Factors among Pregnant Women Attending Antenatal Care at Bwindi Community Hospital, Western Uganda. (7th June 2021) - Nimwesiga, Christine; Murezi, Mereth; Taremwa, Ivan Mugisha
Abstract : Aims/Objectives . This study assessed the adherence to iron and folic acid supplementation and the associated factors among pregnant women attending antenatal care at Bwindi Community Hospital, in Western Uganda. Methods . This was a cross-sectional study that used an interviewer-administered questionnaire and reviewed medical records. Binary and multivariable logistic regression analyses were used to identify factors associated with iron and folic acid supplementation. Adjusted odds ratio (AOR) with 95% confidence interval (CI) and p value < 0.05 were used to assess for statistical significance. Results . We enrolled 438 pregnant women aged 16 to 41years. Participants' mean age (±standard deviation (SD)) was 25.9 (±3.17) years. The self-reported adherence to iron and folic acid supplementation (consumed ≥4 tablets a week or 20 tablets in a month daily without missing the prescribed dosage) was 22.37% (N = 98 ). Among the adherent pregnant women, the reported reasons (and their respective proportionality) for adherence were getting advice and counseling from the healthcare worker about the good effects of iron and folic acid supplementation (N = 34, 34.69%) and knowledge about the health benefits of iron and folic acid supplementation such as preventing anemia (N = 16, 16.33%), among others. On the other hand, the reported reasons (and their respective proportionality) for iron and folic acid nonadherence were forgetfulness (N = 158, 46.47%), taking too many pills (N = 7, 2.06%), not knowing the usefulness of iron and folic acid supplementation (N = 29, 8.53%), fear of the side effects of the medication (N = 119, 35.00%), and not getting the supplement from the hospital (N = 27, 7.94%). Bivariable and multivariable logistic regression analyses indicated that pregnant women who were primigravida (adjusted odds ratio AOR = 4.5 ), who have parity of 2 or 3 (AOR = 3.4 ), who perceived importance of iron and folic acid supplementation to prevent anemia (AOR = 2.9 ), and who considered it important to take iron and folic acid supplementation (AOR = 2.9 ) showed a statistically significant association with adherence to iron and folic acid supplementation. Moreover, pregnant women who perceived the risk of not taking iron and folic acid supplementation (AOR = 5.2 ), those who received sufficient health education regarding the goals of iron and folic acid supplementation as well as the dangers of not taking the supplements (AOR = 4.4 ) and adequate counseling, and those who obtained an explanation of the effects of iron and folic acid (AOR = 4.8 ) showed a significant association with adherence to iron and folic acid supplementation. Conclusion . This study found a low adherence of iron and folic acid supplementation and was associated with obstetric and client- and health system-related characteristics. To this end, there is a need for individualized strategies targeting such factors and intensifying health education, guidance, and counseling to optimize adherence to iron and folic acid supplementation.